The Effect of Competence and Work Motivation on work Satisfaction and Its Effect on Village Apparatus Performance (Study of Village Apparatus in Sakra District, East Lombok Regency) - Syahruddin Syahruddin; Agus Marjan Saputra; Dwi Nur Hidayati; Muhammad Ahyat (Jurnal Ilmiah Sumber Daya Manusia, 2022)
The purpose of this study was to determine and analyze the effect of Competence and Work Motivation on work Satisfaction and their influence on Village Apparatus Performance in Sakra District, East Lombok Regency. The type of research used was explanatory research, because in this study it highlighted the relationship between research variables and tests hypotheses. The populations of this study were 72 village officials in Sakra District, East Lombok Regency. While the sample in this study was a saturated sample or take all members of the population. This was because the research conducted in this study was a census study where this method applied if the population members are relatively small or easily accessible. Data was collected by distributing questionnaires to Village Apparatus in Sakra District, East Lombok Regency. The data analysis technique used in this study was a two-stage regression technique. The results of this study indicated that competence and work motivation have a positive effect on work satisfaction. Likewise, work satisfaction had a positive effect on the performance of Village Apparatus in Sakra District, East Lombok Regency.